Civil Law Contracts and Social Insurance Contributions – Problem Outline - Monika Wałachowska; Jacek Wantoch-Rekowski (Prawo Budżetowe Państwa i Samorządu)
Civil law contracts concluded by two parties have consequences not only in the private law but also in the public law, mainly tax law and social insurance law. In the case of specific-task contracts there can be observed a pro-fiscal approach of the Social Insurance Institution (ZUS), which wrongly claims that some of the specific-task contracts are in fact contract of services and the income should be subjected to social insurance contributions.